2021
DOI: 10.1111/ijfs.15083
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and microbial modulation of phenolic compounds from raspberry leaf extract under in vitro digestion and fermentation

Abstract: Raspberry leaves, by-products in raspberry production, are also a rich source of bioactive phytochemicals. In this study, the changes of phenolic compounds in raspberries leaf extract (RLE) under in vitro digestion and colonic fermentation were further studied by HPLC-MS analysis and 16S rRNA. The results showed that the phenolic compounds in RLE were relatively stable during in vitro gastric digestion; however, in the subsequent intestinal digestion and colonic fermentation, their content decreased sharply. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Our previous results showed that raspberry leaf extract with 50% total phenolic content (TPC) had positive effects on gut microbiota during in vitro digestion and fermentation, and reduced the ratio of Firmicutes/Bacteroidetes and the relative abundance of potential pathogens in the feces of all volunteers. The extract also increased the relative abundance of some bacteria, e.g., Enterococcus and Prevotella, that have been shown to have beneficial value in maintaining intestinal health [6]. Moreover, it was shown to have a potential role in HFD-induced body weight control in mice [7].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous results showed that raspberry leaf extract with 50% total phenolic content (TPC) had positive effects on gut microbiota during in vitro digestion and fermentation, and reduced the ratio of Firmicutes/Bacteroidetes and the relative abundance of potential pathogens in the feces of all volunteers. The extract also increased the relative abundance of some bacteria, e.g., Enterococcus and Prevotella, that have been shown to have beneficial value in maintaining intestinal health [6]. Moreover, it was shown to have a potential role in HFD-induced body weight control in mice [7].…”
Section: Introductionmentioning
confidence: 95%
“…Their adsorption kinetic properties were analyzed using pseudo-first-order (Equation ( 6)) and pseudo-second-order (Equation ( 7)) models. ln q t − q e = −k 1 t + lnq e (6) t q t = 1 k 2 q 2 e + t q e (7) q e is the adsorption equilibrium capacity (mg). q t is the adsorption capacity (mg) at interval time t. k 1 and k 2 are the rate constants of pseudo-first-order kinetic and pseudosecond-order kinetic models, respectively.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, it was shown that the total phenolic content (TPC) of raspberry leaf extract (RLE) reached 540.32 ± 8.96 mg g −1 , and RLE supplementation reduced body weight and adipose percentage in mice after ingestion ( 19 ). In addition, the 16 s RNA sequencing results of co-cultivation of RLE with volunteer feces showed that RLE has potential value in maintaining intestinal health ( 20 ).…”
Section: Introductionmentioning
confidence: 99%